CHARACTERISTICS OF TRAFFIC ACCIDENTS ON 4/2D ROAD TYPES ON THE SURABAYA - MOJOKERTO TOLL ROAD ( CASE STUDY: WARUGUNG - PENOMPO TOLL ROAD SECTION) - Laksono, Achmad Ipung Dwi; Moetriono, Hary (Jurnal Teknik Sipil, 2023)
In developing road infrastructure, keeping pace with the transportation sector and the rapidly growing economy is vital. Inadequate road infrastructure conditions will cause problems on the road, namely traffic accidents and congestion, which results in a lack of driver comfort. PT Jasa Marga can undoubtedly find out the leading cause of the accident. This study aimed to determine the characteristics of traffic accidents on the 4/2d road type, precisely on the Surabaya - Mojokerto toll road on the Warugunung - Penompo toll road. The Surabaya"“Mojokerto Toll Road or Sumo Toll Road is a 36.27-kilometer-long toll road that connects the City of Surabaya with the City of Mojokerto, East Java Province. This toll road is connected to the Kertosono-Mojokerto Toll Road to the west. The class of vehicles on this toll road, such as trucks and large-laden cars, can also be said to be one of the characteristics of traffic accidents. Location of accident-prone points (BlackSpot) on the Warugunung "“ Penompo toll road in 2021 on line A, namely at Km 3+000 "“ 4+000 of the Warugunung "“ Driyorejo section, because at that location there are road slopes and bends, so many motorists drive at high speed high and have to slow down when there is a descent and many riders do not anticipate it. In 2021, line B, namely at Km 5+000 - 6+000 on the Warugunung - penompo section, is not much different from line A.